힙합 문화, 하위문화, 그리고 이들 문화에 대한 사회·문화적 함축성: 독일, 한국 및 미국의 힙합 그룹들에 대한 비교분석을 중심으로 - 게르케 사브리나; 백선기; Gerke, Sabrina; Baek, Seon-Gi (한국콘텐츠학회 논문지, 17(6), 2017)
People are most commonly divided by their nationality, but that does not mean they share the same culture. Even for people from one cultural background, subcultures play an important role for diversity and identity, and popular music is one way to express them. This study analyzed 6 songs of the Hip Hop genre from the US, Germany and South Korea, with one song each from the time of first emergence of the term 'Hip Hop' and one song each from 2016, selected on the basis of popularity indicated by music record sales and specialist literature on the history of Hip Hop. Through semiotic analysis of early and recent Hip Hop in each country, the changes in popular Hip Hop over time were examined. The results of this study show that through standardization, Hip Hop in the three countries has superficially become more similar and more focused on the individual, but on a detailed level shows significant differences: while U.S. Hip Hop refers to the American Dream, German Hip Hop displays an extreme image of masculinity, and Korean Hip Hop deals with private thoughts. Although popular Hip Hop nowadays does not explicitly exercise social criticism it is still ascribed the symbolic significance of a rebellious and revolutionary cultural practice that can be used to criticize and change culture as well as society. 일반적으로 사람들은 자신들이 갖는 국적에 따라 분류되지만, 각 개인의 문화적 경향은 반드시 자신들이 속한 국적에 의해 결정되지 않는다. 오히려 하나의 문화적 배경을 가진 사람이라 하더라도 자신이 속한 하위문화에 따라 자신의 정체성과 다양성이 형성된다. 본 연구는 힙합 장르 노래에 대한 분석을 통해 미국, 독일, 한국의 하위문화적 속성을 밝혔다. 이를 위해 음원 판매액과 힙합의 역사에 관한 기존 연구를 토대로 각 국가에서 힙합이라는 장르가 출현한 시점 및 2016년의 가장 인기 있었던 노래를 각각 한 곡씩 총 여섯곡을 선정해 기호학적으로 분석했다. 국가별 힙합의 초기 및 현재 모습에 대한 비교 분석결과, 흥미롭게도 힙합은 대상에 대한 묘사에 있어 점점 유사해져 가는 동시에, 더욱 개인주의적 경향을 띠고 있음을 공통적으로 지니고 있다. 그러나 세부적인 측면에서 각 국가 간 차이가 발견되었다. 미국 힙합에서는 대표적으로 아메리칸 드림(American Dream)에 대한 열망이 드러났으며, 독일의 힙합에서는 과도한 남성성 이미지가 강조되었다. 한편, 한국 힙합은 보다 일상적인 생각과 이야기를 중심으로 전개되는 양상을 띠었다. 나아가 비록 사회 비판의 도구로서 힙합이 갖는 중요도가 점차 감소하고는 있지만, 여전히 힙합은 강력한 문화적 반항이자 새로운 도전의 상징으로 인식되고 있다.